2012
DOI: 10.1097/jnr.0b013e31827364ec
|View full text |Cite
|
Sign up to set email alerts
|

Nonimaging Clinical Assessment of Impaired Swallowing in Community-Dwelling Older Adults in Taiwan

Abstract: Swallowing function deteriorates with age. Results of this study provide an assessment of the prevalence of impaired swallowing in community-dwelling older adults in Taiwan. Results can help guide clinical nurses to enhance their objective assessment of impaired swallowing to improve patient quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Thirty-four used only one method to estimate SI frequency: three used objective instrumental assessments [4,33,34], seven water and saliva test [22-24, 37, 39, 43], seventeen a screening instrument [18-20, 25, 29, 30, 36, 40, 41, 45-47, 49-51, 54], and seven self-perception [3,16,21,26,38,42,48]. Seven studies presented the estimated frequency of SI by more than one assessment method: one presented by all subtypes [17], two by objective assessment, water test, and a screening instrument [28,37], and four presented by water test and a screening instrument [27,32,44,53]. The lowest estimated frequency of SI was found by Zhang H. et al 2020 [44], 5.5% assessed by Eating Assessment Tool (EAT-10), followed by Mulheren et al 2018 [28], 6.4%, assessed by videofluoroscopy and Penetration/Aspiration Scale in the USA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-four used only one method to estimate SI frequency: three used objective instrumental assessments [4,33,34], seven water and saliva test [22-24, 37, 39, 43], seventeen a screening instrument [18-20, 25, 29, 30, 36, 40, 41, 45-47, 49-51, 54], and seven self-perception [3,16,21,26,38,42,48]. Seven studies presented the estimated frequency of SI by more than one assessment method: one presented by all subtypes [17], two by objective assessment, water test, and a screening instrument [28,37], and four presented by water test and a screening instrument [27,32,44,53]. The lowest estimated frequency of SI was found by Zhang H. et al 2020 [44], 5.5% assessed by Eating Assessment Tool (EAT-10), followed by Mulheren et al 2018 [28], 6.4%, assessed by videofluoroscopy and Penetration/Aspiration Scale in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Some included studies showed frequency data by more than one assessment method. Six studies [4,17,26,[31][32][33] showed data for objective measures, thirteen for water test or saliva [17, 22-24, 26-28, 32, 35, 37, 39, 43, 44, 53], twentyfive for screening questionnaires [17-20, 25, 27-32, 35, 36, 40, 41, 44-47, 49-54], and nine for single-item self-report [3,16,17,21,26,31,38,42,48]. The pooled effect for each assessment method is shown in Fig.…”
Section: Frequency By Assessment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 11.8 million older adults live alone and may be considered CDOA [3,6]. A growing body of evidence suggests CDOA are at risk for developing dysphagia with potential prevalence rates as high as 35% [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. These conservative estimates suggest that within the US alone, CDOA at risk for developing dysphagia may be in excess of 4 million.…”
Section: Introductionmentioning
confidence: 99%